1980
DOI: 10.1002/1097-0142(19801101)46:9<2047::aid-cncr2820460924>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activities in human fetal and neoplastic tissues

Abstract: The concentrations of ten or 12 enzymes involved in the metabolism of DNA, collagen, amino acids, or glucose have been determined in variants of human intestinal and pulmonary tissues. In comparison to nonneoplastic adult colon, normal fetal colon had elevated concentrations of thymidine kinase, peptidyl proline hydroxylase, phosphoserine phosphatase, ornithine transcarbamylase, gamma-glutamyl transpeptidase, and ornithine aminotransferase. Raised activities of the first five of these enzymes, and of hexokinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…hexokinase, phosphoglucoisomerase and aldolase in cancer induced rats. This infers that the rate of glycolysis was enhanced during tumour growth (19). There exists a direct correlation between glycolytic activity and hexokinase in a variety of tumour cell lines (20).…”
Section: Discussionmentioning
confidence: 88%
“…hexokinase, phosphoglucoisomerase and aldolase in cancer induced rats. This infers that the rate of glycolysis was enhanced during tumour growth (19). There exists a direct correlation between glycolytic activity and hexokinase in a variety of tumour cell lines (20).…”
Section: Discussionmentioning
confidence: 88%
“…The cytosolic enzyme TK1, dominates in replicating cells, but is absent in resting cells (Bello, 1974). Therefore high levels of TK1 activity are found in foetal and neoplastic cells, but its activity is low in non-growing adult tissue (Gordon et al, 1968;Herzfeld & Greengard, 1980;Bardot et al, 1991). The second type of the enzyme, TK2, is of mitochondrial origin and causes the lower and constant level of TK activity in resting cells (Adler & McAuslin, 1974).…”
mentioning
confidence: 99%
“…We Sakamoto et al (1984Sakamoto et al ( , 1985 and others (Herzfeld et al 1978 ;Herzfeld and Greengard 1980 ;Waber et al 1980Waber et al , 1981 have previously determined that total TK activity in human colon carcinoma tissue was significantly higher than that seen in normal human colon mucosa. Weber et al (1980) have reported that TK activity rises to 331% that of normal mucosa in colonic adenocarcinoma samples obtained from nine patients, and that TK activities in rapidly growing xenografts of human colon carcinoma in nude (athymic) mice were markedly higher than those in slowly growing xenografts (Weber et al 1981).…”
Section: Discussionmentioning
confidence: 60%
“…Weber et al (1980) have reported that TK activity rises to 331% that of normal mucosa in colonic adenocarcinoma samples obtained from nine patients, and that TK activities in rapidly growing xenografts of human colon carcinoma in nude (athymic) mice were markedly higher than those in slowly growing xenografts (Weber et al 1981). Furthermore, Herzfeld et al (1978), Herzfeld and Greengard (1980) have also suggested that progressive elevations in TK activity seem to correlate with increasing histological dedifferentiation of the tumor.…”
Section: Discussionmentioning
confidence: 99%